A gestão da relação escola-comunidade - Castro, Megione Bassetto de (2016)
This dissertation named "The Management of School-Community Relations", based on the critical theory of Theodor W. Adorno, has as its object of study the relationship between the school investigated and the community of Vargem Grande. The question that guides this research, is if the mechanisms of management, school-community relationship, existing in the research school ensures the management of this relationship and the consequent care to community demands by the school. The hypotheses suggest there elements and variables that can create noise in the management of this relationship as conflict, administered culture and pseudo-formation of subjects involved and that existing mechanisms in school for guaranteeing school-community relationship, does not guarantee management effective this relationship. The general objective is to investigate the mechanisms of school-community relationship management: the School Council, Class Council and Series, Parent Teacher Association and the Student Government, the latter created by the intervention proposal resulting from this research. Some specific objectives have been established to achieve the general objective, how to parse if the direction of the school investigated is characterized by the dialectic proposed of resumption of sensitization and reflection, as well as others. The methodology of empirical research involved the use of techniques associated with the community study involving a literature review of community history and the studied school, also doing a survey of several other theoretical and academic papers related to the topic, characterizing a case study, where the individual situation is studied in depth to provide a broader understanding of other cases. The results allowed us to confirm our hypothesis that the existence of these management mechanisms, does not automatically guarantee a democratic and participatory management, since it does not happen on a regular basis the ordinary or extraordinary convocations of the School Council, Parent Teacher Association and the Student Government.